Silicon fertigation alleviates salinity stress by enhancing morpho-physiological, photosynthetic, antioxidative responses, and yield in mung bean (Vigna radiata L.) varieties Co7(Gg) and Co8 under pot and field conditions - Sadhanandan, Sushilkumar; Bae, Dong Won; Prakash, Muthu Arjuna Samy; Muneer, Sowbiya (Frontiers in Plant Science, 2025)
IntroductionSilicon (Si), the second most prevalent element in the earth, is not soluble enough for plants to absorb, despite being one of numerous helpful elements. Supplementing with silicon (Si) is seen to be one of the most promising ways to mitigate abiotic stressors like salt and drought. Legume crops are still underutilised, especially mung bean, an important crop in India, despite several research on the effects of salt and silicon stress on various crops.MethodsIn order to study the impact of exogenous application of Si concentrations on the growth and physiochemical, Photosynthetic efficiency, and antioxidative pathways of four mung bean cultivars—K1, Co6, Co7Gg, and Co8 exposed to two levels of salinity] [10 mM NaCl, 20mM NaCl and 5 mM of Si—a Pot experiment and field data were collected over the course of two growth seasons (2023–2024). The overall treatments given were in six combinations as: (i) -Si/-NaCl (control) (ii) -NaCl + Si (iii) 10mM NaCl/−Si (IV). 10 mM NaCl/+ Si (v) 20mM NaCl/-Si (vi) = 20mM NaCl/+Si Growth factors like biomass, plant length, height, and photosynthetic measurements were all lowered by salinity stress; however, these effects were lessened by silicon supplementation at a concentration of 5 mM sodium silicate.Results and discussionUnder salt stress, the presence of silicon boosted the production of photosynthetic proteins such Photosystem I, Photosystem II, and light harvesting complexes. In the mung bean, salinity stress also resulted in oxidative damage in the form of superoxide radical (O2−) and hydrogen peroxide (H2O2), which raised MDA (lipid peroxidation) and electrolyte leakage. On the other hand, 5 mM sodium silicate has the ability to scavenge free radicals, which lowers electrolyte loss and lipid peroxidation (MDA). Significant silica deposition in the leaf epidermis was associated with this, and in the end, this served as a mechanical barrier to lessen the harmful effects of salt stress. Our simulated investigations, which employed Si as a supplement, indicated that, of all the varieties used in this study, K1 and Co7Gg shown resilience to salt stress, but Co6 and Co8 showed sensitivity. Experiments conducted at the field level on yield and growth provided evidence for the study's findings that Si has a positive impact on salt stress. Si reduced the detrimental effects of salt stress and provided a basic idea for using Si as a fertilizer.